2004
DOI: 10.2165/00007256-200434030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Training Effects on Blood Haemostasis in Health and Disease

Abstract: In recent years, the dysfunction of the haemostatic system in relation to the clinical complications from arterioscleroses and cardiovascular diseases has become more recognised. Blood coagulation and fibrinolysis comprise two important physiological systems, which are regulated by a balance between activators and inhibitors. Activation of blood coagulation is associated with accelerated clot formation, whereas activation of blood fibrinolysis enhances the breakdown of the blood clot. Available evidence sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
107
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 128 publications
6
107
1
5
Order By: Relevance
“…Additionally, artifacts resulting from blood sampling and handling can induce elevated b-TG and PF4 levels in plasma [32]. Although investigations showed that b-TG and PF4 concentrations increased following acute exercise [33,34], other studies did not identify significant changes in the ratio of b-TG to PF4 after exercise [18]. Therefore, this finding suggests that platelet secretion in vivo was not directly activated by exercise.…”
Section: Effects Of Acute Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, artifacts resulting from blood sampling and handling can induce elevated b-TG and PF4 levels in plasma [32]. Although investigations showed that b-TG and PF4 concentrations increased following acute exercise [33,34], other studies did not identify significant changes in the ratio of b-TG to PF4 after exercise [18]. Therefore, this finding suggests that platelet secretion in vivo was not directly activated by exercise.…”
Section: Effects Of Acute Exercisementioning
confidence: 99%
“…The b-adrenergic pathway has been implicated as a pathway potentially mediating an exercise-induced increase in FVIII levels as b-blockade blunts this increase [62]. Some investigations showed that aerobic and anaerobic exercise increases plasmin formation, possibly by increasing plasminogen activator (t-PA) and reducing plasminogen activator inhibitor (PAI-1) [34,63], thereby accelerating the blood fibrinolysis rate and enhancing fibrin degradation. Although b-adrenergic receptor blocking by propranolol partially reduces normal fibrinolytic response to strenuous exercise [64], t-PA release occurs prior to an increase in blood catecholamine concentration, suggesting that the initial release of t-PA induced by exercise is mediated by another non-adrenergic mechanism -possibly vasopressin [65].…”
Section: Effects Of Acute Exercisementioning
confidence: 99%
“…Since moderate physical exercise is known to lower the risk of cardiovascular diseases [9,10], we were interested to study the effect of moderate physical exercise on both concentration and pro-coagulant activity of circulating MP.…”
mentioning
confidence: 99%
“…Its accurate mechanism during any kind of exercise is not actually clear. Most likely, some mechanical factors can be involved in this process, such as an increase in cardiac output, and cause some changes in capillary endothelial cells (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the effects of exercises on platelet concentration and symptoms of platelet activation. However, it has to be mentioned that short-term training causes activation of blood clotting, as well as an increase in fibronolize, and maintains the balance between formation of blood clotting and its analysis in a natural level (10,15). Based on the finding of the present study, it can be concluded that even though PLT and LYM had dropped down to their lower levels during the 45-and 90-minute recovery, WBC, at the same time, showed a significant increase, which manifests the partial weakening of the immune system of the body.…”
Section: Discussionmentioning
confidence: 99%